(untitled) (Teología, 2022)
In this paper we will analyze the parliamentary debate of the Senate on May 18, 1876, due to a request for financial aid for the repair of the College "del Salvador" of the Society of Jesús in Buenos Aires, which had been burned down the year previous. In this debate we will focus on the performance of Domingo Faustino Sarmiento, who was serving as senator for the province of San Juan, noting his opinions and arguments against the Society of Jesús. To arrive at these considerations, we will first and briefly stop at the relationship between San Juan and freemasonry and the Jesuits. The objective will be to give a brief contribution more in the way of the investigation of the religious profile of Sarmiento and his performance in freemasonry, in the context of his national political performance